Varadouros indígenas, percursos indigenistas: relatos e perspectivas sobre o isolamento dos povos indígenas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The "isolation" of indigenous peoples is a topic that is widely approached in State policies, in civil society, in academia, and in the media. In the villages and indigenous assemblies, the debate about the "isolated" "relatives" also occurs and, many times, the subject is treated in a heated way, because it is usually linked to the discussions about indigenous territories (and their protection). The ways in which indigenous people relate to their territories (territorialities), in this sense, are articulated and influenced by the manner, peaceful or not, in which they interact with other indigenous groups or with non-indigenous - the State and surrounding populations - that, in turn, put pressure on their territories. Based on different ethnographic experiences, provided by indigenist journeys as a Funai servant in the Amazon region between 2006 and 2018 - from Acre to Maranhão -, recorded in field diaries, intertwined with indigenous and indigenist accounts available in bibliography and documentation, it is possible to see that "isolation" - in its various forms - can be synonymous with "contact" and that the mobilization of these concepts occurs not only in relation to Amerindian collectives so categorized by the State, but to all indigenous peoples. A deep understanding of what "isolation" or "contact" means can reveal, like a magnifying glass, some particles that constitute the persistent genocidal and ethnocidal process on indigenous peoples. If so, the continuous and well-known indigenous resilience (the "isolation"?) would occur from - and be the proof, therefore - of the persistent genocidal and ethnocidal complex.
Keywords: Política Indigenista; Povos Indígenas Isolados; Resiliência Indígena; Genocídio Indígena; Indigenismo; CNPQ:: CIÊNCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA::TEORIA ANTROPOLÓGICA; SOCIEDADES AMAZÔNICAS, SISTEMAS CULTURAIS E SOCIABILIDADES; SOCIEDADES AMAZÔNICAS, SISTEMAS CULTURAIS E SOCIABILIDADES